Primary orbital Ewing sarcoma family of tumors: a study of 12 cases - Kaliki, S (Eye (Lond), 2018)
PURPOSE: The purpose of this study is to discuss the clinical presentation, management, and outcomes of patients with primary orbital Ewing sarcoma family of tumors (ESFTs). PATIENTS AND METHODS: Retrospective study of 12 patients with biopsy-proven primary orbital ESFT. RESULTS: The mean age at presentation of primary orbital ESFT was 12 years (median, 8 years; range, 5 months to 28 years). There were seven (58%) females and five (42%) males. The presenting complaints included proptosis (n=10; 83%) and swelling in the upper eyelid (n=2; 17%). The mean duration of symptoms was 9 weeks (median, 5 weeks; range, 2–24 weeks). Tumor epicenter was located in the superior orbit (n=6; 50%), lateral orbit (n=3; 25%), inferior orbit (n=2; 17%), and medial orbit (n=1; 8%). Computed tomography of the orbits revealed predominant bony lesion (n=10; 83%) or isolated soft tissue/extraosseous lesion (n=2, 17%). At presentation, extraorbital extension was noticed in 10 patients including intra cranial extension (n=7; 58%), extension into temporal fossa (n=4; 33%), nasal cavity (n=2; 17%), maxillary sinus (n=2; 17%), and ethmoid sinus (n=1, 8%). Systemic metastases at presentation was detected in five (42%) patients involving the bone marrow (n=4; 33%), kidney (n=1; 8%), and retroperitoneal lymphnode (n=1; 8%). Multi-modal treatment including a combination of neoadjuvant chemotherapy, excision biopsy/debulking, and/or radiotherapy was given. Over a mean follow-up period of 21 months (median, 7 months; range, 1–152 months), disease-related death occurred in 11 (92%) cases. CONCLUSION: Primary orbital ESFT is aggressive at presentation and is associated with poor prognosis.